PENGARUH FASILITAS, DAYA TARIK WISATA DAN AKSESBILITAS TERHADAP KEPUTUSAN WISATAWAN BERKUNJUNG KE TAMAN HERBAL INSANI DEPOK - Citra Nur Sabrina Izzati; Dinda Nisaa Ramadaniyah; Elfira Rosmiati (Sekolah Tinggi Pariwisata Mataram, 2022)
This study aims to analyze the influence of facilities, attractiveness and accessibility on the decision of tourists to visit the Insani Herbal Park in Depok. This study uses a qualitative method with purposive data source collection, data collection techniques with data collection in a natural setting with the intention of interpreting the phenomena that occur where the researcher is the key instrument, purposive data source collection, triangulation (combined) collection techniques, data analysis is inductive/qualitative, and qualitative research results emphasize meaning rather than generalization. The results of this study indicate that facilities, attractiveness, and accessibility partially affect the research. And the results of the analysis together show that facilities, attractiveness, and accessibility affect the decision to visit.